Microbial Biomass Responses to Soil Drying-Rewetting and Phosphorus Leaching - Khan, Sidra U.; Hooda, Peter S.; Blackwell, Martin S. A.; Busquets, Rosa (Frontiers in Environmental Science, 2019)
Soil drying-rewetting is known to enhance soil phosphorus leaching, which in part is due to osmotic shock and lysis of microbial cells upon rewetting. However, it is not entirely clear how this may be influenced by the intensity and duration of soil drying. We hypothesized that the intensity and duration of soil drying play important roles in determining the extent of dissolved reactive phosphorus (DRP) leaching resulting from microbial biomass mortality. To test this hypothesis soil sub-samples of a loamy grassland soil were dried (30C or 40C for 2-days or 14-days), rewetted, and the leachate was analysed for DRP. Soil drying at 30C for 2-days and 14-days resulted in leachate DRP concentrations which were 71% and 271% respectively higher than those in leachate from a control moist counterpart. Relatively greater DRP leaching losses occurred from the soil dried at 40C for 2-days and 14-days (143% and 300% respectively). To determine the contribution of the microbial biomass to the DRP in leachate, soil sub-samples were fumigated with chloroform either before or after drying (30C or 40C for 2-days or 14-days). All soil treatments were then either leached with water and analysed for DRP or extracted with 0.5M sodium bicarbonate solution and analysed for microbial biomass phosphorus. Fumigating soil samples before or after drying reduced microbial biomass phosphorus. However, the effect of chloroform fumigation was more pronounced in terms of microbial biomass reduction in the DF (drying followed by fumigation) treatment. Moreover, results revealed that in the DF treatment, soils dried at 30C for 2-days and 14-days had 22% and 13% respectively more microbial biomass phosphorus than their counterparts dried at 40C for 2-days and 14-days respectively. These results suggest that soil drying at higher intensity and for prolonged periods significantly (p<0.05) affect microbial biomass and subsequently increases soil phosphorus leaching following rewetting, due to enhanced contributions from the microbial biomass. These findings, however, need to be verified over a range of soil types under natural field conditions to better assess soil drying-rewetting effects on nutrient leaching.